SISTEM INFORMASI MANAJEMEN KLINIK PADA KLINIK PRATAMA “RUMAH SEHAT” - Iis Istiqomah; Okta Irawati (BULLET : Jurnal Multidisiplin Ilmu, 2023)
The data management system of clinical data that is still done manually, requires a long time and not accurate so that sometimes there are some income or expenses that have not yet been recorded. In addition to the data management of clinical data, data search also still done manually. Data search patients and medical records of patients who had treatment before need a long time because the amount of data of patients who registered and the accumulation of medical record data enough. The other problem is not the media that cover on the information from the Klinik Pratama "Rumah Sehat" as the clinic profile, practice schedule each doctors, services and facilities in the Klinik Pratama "Rumah Sehat". The method used is a descriptive method, namely methods that examine an object, a set of conditions, a thought or an event in the class now that aims to create a descriptive or a description systematically, based on the fact and detail. After tested, can be known that outline this system can resolve the problem found in the clinic pratama covering registration, queues, consulting medical records and reports. So in general the system can provide the solution to the user and the system is running in accordance with the expected.